High School Students' Scientific Literacy in the Context of Covid-19 Pandemic - Mega Elvianasti; Nifa Nisfaturahmah; Irdalisa Irdalisa; Maesaroh Maesaroh (AL-ISHLAH: Jurnal Pendidikan, 2022)
Many previous researchers have indeed done research related to scientific literacy. However, few studies discuss scientific literacy related to the context of the COVID-19 virus on biological materials. The goal of this study is to find out how well students understand science in the context of the COVID-19 virus. The descriptive quantitative research method was applied. The sample consisted of 107 students from class XI science at a Madrasah Aliyah in Tangerang Selatan. The results showed the students' scientific literacy ability with an average percentage of 75.65% with good interpretation. Scientific literacy tested are 73.89% contextual aspects with sufficient interpretation, knowledge aspects, 75.29% with adequate interpretations, 75.47% competence aspects with sufficient interpretations, and 84.35% with good interpretations. The study concludes that students in class XI science can comprehend scientific literacy in the context of a current scientific occurrence, namely, the COVID-19 virus. The findings have implications for how teachers can develop students' scientific literacy skills by providing contextual examples of the COVID-19 virus so that students understand it and apply it in everyday life.